2012
DOI: 10.1124/jpet.112.198747
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide-Induced Catecholamine Release from Cardiac Sympathetic Neurons: Inhibition by Histamine H3 and H4 Receptor Activation

Abstract: We reported previously that natriuretic peptides, including brain natriuretic peptide (BNP), promote norepinephrine release from cardiac sympathetic nerves and dopamine release from differentiated pheochromocytoma PC12 cells. These proexocytotic effects are mediated by an increase in intracellular calcium secondary to cAMP/protein kinase A (PKA) activation caused by a protein kinase G (PKG)-mediated inhibition of phosphodiesterase type 3 (PDE3). The purpose of the present study was to search for novel means to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
15
2
Order By: Relevance
“…The K þ -and BNP (brain natriuretic peptide)-induced release of norepinephrine (NE) from cardiac synaptosomes was inhibited by methimepip (H 3 R agonist) as well as by the H 2 R/H 4 R agonist 4-MH. The 4-MH-induced effect was effectively blocked by the H 4 R antagonist A 943931, which suggests that it was not caused by unspecific H 2 R activation (Chan et al, 2012). Unfortunately, however, Chan et al (2012) did not record a complete concentrationeeffect curve for 4-MH, and therefore, concentration dependency of the effect could not be established.…”
Section: H 4 R Expression On Other Peripheral Neuronsmentioning
confidence: 63%
See 2 more Smart Citations
“…The K þ -and BNP (brain natriuretic peptide)-induced release of norepinephrine (NE) from cardiac synaptosomes was inhibited by methimepip (H 3 R agonist) as well as by the H 2 R/H 4 R agonist 4-MH. The 4-MH-induced effect was effectively blocked by the H 4 R antagonist A 943931, which suggests that it was not caused by unspecific H 2 R activation (Chan et al, 2012). Unfortunately, however, Chan et al (2012) did not record a complete concentrationeeffect curve for 4-MH, and therefore, concentration dependency of the effect could not be established.…”
Section: H 4 R Expression On Other Peripheral Neuronsmentioning
confidence: 63%
“…Moreover, Chan et al (2012) conclude from a Western blot analysis that PC12 rat pheochromocytoma cells constitutively express H 4 R, but as already mentioned several times in our article, antibody staining results should be interpreted with caution. Unfortunately, H 4 R-free cells (e.g.…”
Section: H 4 R Expression On Other Peripheral Neuronsmentioning
confidence: 74%
See 1 more Smart Citation
“…We recently ascertained the presence of H 4 Rs in cardiac sympathetic nerve endings where, similar to H 3 Rs, H 4 Rs inhibit NE release (Chan et al, 2012). This effect could complement the reduction of NE release ultimately resulting from H 4 R-mediated actions at the MC level.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, in addition to the heart, H 4 R-mediated protective mechanisms may impact other organs (e.g., brain, liver, and kidney) that have renin-containing MCs (Reid et al, 2007;Biran et al, 2008;Veerappan et al, 2008), can suffer ischemic episodes (Kaneko et al, 1998;Guo et al, 2004;Chen et al, 2009), and have been shown to be protected by IPC (Nandagopal et al, 2001;Adachi et al, 2006;Chan et al, 2012;Kukreja, 2012). Fig.…”
Section: Discussionmentioning
confidence: 99%